Beginning early mathematical modelling in Early Childhood Education: how do 3-year-olds think and what do they do? (Edma 0-6: Educación Matemática en la Infancia, 2022)
Early mathematical modelling, defined as a process that helps to create the first models to analyse, explain and understand reality, is an ideal framework for developing mathematical competence. From this point of view, the activity "we build houses with pieces of wood", which has been implemented with 20 3-year-old children, is presented. In order to analyse the modelling cycle, the indicators of the "Rubric for the Evaluation of Mathematical Modelling Processes" were used. The results show that 3-year-olds begin to develop skills of comprehension, structuring, mathematization, mathematical work, interpretation, validation and exposition and, therefore, create the first concrete models. It is concluded that, in future studies, it is necessary to determine the influence of several variables on children's actions, such as the type of task or the knowledge of the Early Childhood Education teacher to carry out early mathematical modelling activities.
Keywords: Early mathematical modelling; modelling cycle; concrete model; mathematics teaching; Early Childhood Education